2006
DOI: 10.1021/bc060038m
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis Of Ferrocene Probe Molecules for Detection by Electrochemical Methods

Abstract: A series of ferrocenyl conjugates to fatty acids have been designed and synthesized to establish the key properties required for use in biomolecular binding studies. Amperometric detection of the ferrocene conjugates was sought in the region of 0.3 V (vs Ag/AgCl) for use in protein/blood solutions. Different linkers and solubilizing moieties were incorporated to produce a conjugate with optimal electrochemical properties. In electrochemical studies, the linker directly attached to the ferrocene was found to af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
(59 reference statements)
2
9
0
Order By: Relevance
“…Electrochemical detection of biomolecules is of special interest due to their low cost, miniaturization, rapidity, and sensitivity. [33][34][35][36][37] Moreover, the self-assembly of the block copolymer-biomolecule conjugates may induce redox-responsive micelles, which may change their physical parameters such as shape or size in response to redox reactions. Therefore, as well as the synthesis, the conjugation of a model drug O-benzylhydroxylamine was also demonstrated as an example of how the new block copolymer can be utilized to conjugate bioactive molecules by aldehyde groups and subsequently quantify the degree of the conjugation by ferrocene moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical detection of biomolecules is of special interest due to their low cost, miniaturization, rapidity, and sensitivity. [33][34][35][36][37] Moreover, the self-assembly of the block copolymer-biomolecule conjugates may induce redox-responsive micelles, which may change their physical parameters such as shape or size in response to redox reactions. Therefore, as well as the synthesis, the conjugation of a model drug O-benzylhydroxylamine was also demonstrated as an example of how the new block copolymer can be utilized to conjugate bioactive molecules by aldehyde groups and subsequently quantify the degree of the conjugation by ferrocene moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Melting points are uncorrected. 1 H NMR and 13 C NMR spectra were recorded in CDCl 3 at the field indicated unless otherwise indicated. 1-Bromo-14-(tetrahydropyran-2-yloxy)tetradecane was prepared as previously described (18).…”
Section: Syntheses Of Compounds Based On the General Structure 2 But ...mentioning
confidence: 99%
“…After evaporation in vacuo, the product was purified by flash silica chromatography (hexane/EtOAc, 1:1) to give 2-(14-hydroxytetradecyl)-isoindole-1,3-dione (37 mg, 67%) (17). 1 H NMR (300 MHz; CDCl 3 ) 1.29 (m, 18H), 1.60 (m, 6H), 3.60 (m, 4H), 7.68 (m, 2H, ArH), 7.78 (m, 2H, ArH); 13 To 2-(14-hydroxytetradecyl)-isoindole-1,3-dione (37 mg, 0.10 mmol) in acetone (1 mL) was added Jones reagent (0.085 mL; for 1 mL of Jones reagent-0.23 mL H 2 SO 4 , 270 mg CrO 3 , 0.77 mL H 2 O). The reaction was stirred at rt for 1 h, 2-propanol (5 mL) was added and the mixture diluted with water (5 mL), then the acetone removed in vacuo.…”
Section: Syntheses Of Compounds Based On the General Structure 2 But ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis and applications of ferrocenyl-substituted benzene have been pursued for several years [9,10]; we found that some phenomena can be elucidated through electrochemical properties of ferrocene [11][12][13]. Therefore, ferrocene could be used as an electrochemically sensitive probe to detect the electron density of the benzene ring [14,15]. Though tricarbonylchromium complex before, the influence of the tricarbonylchromium unit on the electrochemical properties of ferrocene was not studied [8].…”
Section: Introductionmentioning
confidence: 99%